(a+b)(a-b) = a^2 - b^2 not other things.Owen here.
It is supposed to be -b^2 as it is a +b multiplied by -b
The second question should make use of algebra to find the answer .
You should have kind of guessed that the second question is actually trying to test you using the method in first part to solve second question...That kind of method you did we won't know if you used calculator or not also...
- b x b = -b^2negative and positive = negative.
It should be -b^2 instead as -b* b = -b^2
It should be -b^2 as negative x positive = negative
suppose to be -b^2 since its -b mutliply by b
It should have been -b^2 as -b x b = -b^2For the second part, the numbers can represent a letter.a = 100b = 5You can substitue the numbers thus, you can get -b^2.
it should be a^2+ab-ab-b^2 instead of what is stated
7b should make use of the equation in 7a, as the question states hence, which is referring to 7a
7a should be -b^2. 7b should make use of 7a to find the solution
You must use part a to help solve
1st ERROR: -b x b = -b^2, not b^22nd ERROR: Use the method in a) to solve b)
b(-b)=-b^2Part (b) should be solved using (a+b)(a-b)-a^2
Question 7a should be -(b^2). You should make use of 7a to help find the answer in 7b.
as it is hence - you must use a method related to (a) to answer the question
You should be using the solution in (a) to solve (b) because they used the word HENCE
(a+b)(a-b) = a^2 - b^2you need to use the method of (a) to solve (b).If you do not, we can just press the calculator and that does not know we know the skills. So, no marks are given
1. -b x b = -b^2 not b^2
(a) The term b^2 should be -b^2 when expanded.(b) He did not make use of the answer in (a) to solve the question.